If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 = 6x + -4y Solving 24 = 6x + -4y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 24 + -6x = 6x + -6x + -4y Combine like terms: 6x + -6x = 0 24 + -6x = 0 + -4y 24 + -6x = -4y Add '-24' to each side of the equation. 24 + -24 + -6x = -24 + -4y Combine like terms: 24 + -24 = 0 0 + -6x = -24 + -4y -6x = -24 + -4y Divide each side by '-6'. x = 4 + 0.6666666667y Simplifying x = 4 + 0.6666666667y
| s^2-11s+30=0 | | 5(2x-14)+23=7x-14 | | 10a(2-7a)= | | x(6)+y(4)=24 | | 3(y-4)-5=-2 | | 7(2+5)=x | | x(6)+y(y)=24 | | n-2+n+2=0 | | 4(y+3)=48 | | 3x+2(x-9)=8x+x-14 | | -10-3x=-10 | | 80(x-8)=48(x+8) | | 4=h+2 | | 6=5p-5-4p | | 4z^2+5z-6=0 | | 7x+2y=23 | | 5x+10-8=4x-2 | | -3y+3y+4=4 | | -6=2+b | | 4x+4=3x-2 | | 6(h+1.5)-1=4h-8 | | -1=-4(b-2) | | 28x-7=5x+11 | | 4(2x+14)=0 | | 6x-5=3x-1 | | 2x+9=5+4x | | -4a+12a-3a= | | -3(x+5)=3(7+3t) | | 3a-14=61 | | 6a^5+37a^3b^2+6ab^4=0 | | x+y+z=410 | | 12x^3y+10x^2y-8xy=0 |